Large deviations for unbounded additive functionals of a Markov process with discrete time (noncompact case). (1994) - Gulinskii, O. V.; Lipster, Robert S.; Lototskii, S. V.
Abstract : We combine the Donsker and Varadhan large deviation principle (l.d.p) for the occupation measure of a Markov process with certain results of Deuschel and Stroock, to obtain the l.d.p. for unbounded functionals. Our approach relies on the concept of exponential tightness and on the Puhalskii theorem. Three illustrative examples are considered.